PREGNANCY IN TIMOR CULTURAL VIEWS (ATONI) - DEWA AYU PUTU MARIANA KENCANAWATI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
Utilization of health facilities in the city of Kupang considerably lower than the national target. Kota Kupang in Timor tribes still adhere to and practice some cultural practices related to the life cycle that will affect how people view pregnancy Timor. This study aimed to describe pregnancy is seen by Timorese culture (Atoni). This study used phenomenological qualitative approach, sampling in this study using purposive sampling technique, the data were collected through interviews and analyzed thematically. Results obtained interview Timorese culture view pregnancy is the nature of women and all women are required to get pregnant, but her husband and family also play a role to care for and maintain the pregnancy but for prenatal care at the health center during their pregnancy despite still do massage in a trusted shaman family.